Keeping watch in Babylon : the astronomical diaries in context - Haubold, Johannes,; Steele, John M.,; Stevens, Kathryn, 1986- (Culture and History of the Ancient Near East, 2019)
This volume of collected essays, the first of its kind in any language, investigates the Astronomical Diaries from ancient Babylon, a collection of almost 1000 clay tablets which, over a period of some five hundred years (6th century to 1st century BCE), record observations of selected astronomical phenomena as well as the economy and history of Mesopotamia and surrounding regions. The volume asks who the scholars were, what motivated them to 'keep watch in Babylon' and how their approach changed in the course of the collection's long history. Contributors come from a range of disciplinary backgrounds, including Assyriology, Classics, ancient history, the history of science and the history of religion.